Prevalence, Awareness, and Control of Hypertensive Disorders amongst Pregnant Women Seeking Healthcare in Ghana - Pauline Boachie-Ansah; Berko Panyin Anto; Afia Frimpomaa Asare Marfo; Edward Tieru Dassah; Constance Caroline Cobbold; Morrison Asiamah (Journal of Pregnancy)
Hypertensive disorders in pregnancy (HDPs) are no longer seen as “transitory diseases cured by delivery.” It accounts for up to 50% of maternal deaths. Information concerning HDPs is less in developing countries like Ghana. This study was conducted to find out the prevalence, awareness, risk factors, control, and the birth outcomes of HDPs. This was a retrospective cohort study conducted among pregnant women seeking care in selected health facilities in the Ashanti Region. Data on demographics, HDPs, and its associated birth outcomes were collected. Logistic regression models were used to examine the association of the independent variables with HDPs. The burden of HDPs was 37.2% among the 500 mothers enrolled with chronic hypertension superimposed with preeclampsia accounting for 17.6%, chronic hypertension, 10.2%, and preeclampsia 6.8% whilst gestational hypertension was 2.6%. It was observed that 44% (220) of the mothers had excellent knowledge on HDPs. Oral nifedipine and methyldopa were frequently used for HDP management, and it resulted in a significant reduction in HDP burden from 37.2% to 26.6%. Factors that influenced the increased risk of HDPs were grand multigravida (AOR=4.53; CI=1.42–14.42), family history of hypertension (AOR=3.61; CI=1.89–6.90), and the consumption of herbal preparations (AOR=2.92; CI=1.15–7.41) and alcohol (AOR=4.10; CI=1.34-12.62) during pregnancy. HDPs increased the risk of preterm delivery (AOR=2.66; CI=1.29–5.89), stillbirth (AOR=12.47; CI=2.72–57.24), and undergoing caesarean section (AOR=1.70; CI=1.10–2.61) amongst mothers during delivery. The burden of HDPs is high amongst pregnant mothers seeking care in selected facilities. There is the need for intensified campaign on HDPs in the Ashanti Region of Ghana.